Групповая работа как эффективное средство саморегуляции обучающихся - Ныгметова, Б.Ж. (My University, 2016)
This article is devoted to the problem of action research. The group work is presented as selfregulation of the students.
Keywords: self-regulation; group work; reflection; action research